Brodalumab-an IL-17RA monoclonal antibody for psoriasis and psoriatic arthritis. (June 2015) - Bauer, Erin; Lucier, Jessica; Furst, Daniel E
<x xml:space="preserve">Abstract</x> Introduction: IL-17 is a growing target for autoimmune and inflammatory diseases. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Brodalumab&logicalOpe1=OR&field2=articletitle&text2=Brodalumab&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Brodalumab is a fully human anti-IL-17RA monoclonal antibody that has been investigated in a range of disease including psoriasis, psoriatic arthritis, rheumatoid arthritis, inflammatory bowel disease and asthma. Areas covered: This review aims to summarize up-to-date pharmacological properties of brodalumab and the clinical efficacy and safety data presented in clinical trials. The focus of this review will be on psoriasis, psoriatic arthritis and rheumatoid arthritis although we will briefly touch on the other indications in which the drug has been studied as we feel it adds to our understanding of the IL-17 pathway and highlights areas where research is still needed. Expert opinion: Brodalumab has shown good efficacy in psoriasis in small but extended studies with a moderate effect on psoriatic arthritis. Brodalumab studies are clearly negative in rheumatoid arthritis and inflammatory bowel disease. The data are equivocal in asthma; however, further studies in this disease are justifiable. The safety profile of this drug thus far is not worrisome although longer studies in more patients are needed.